Facial frictional melanosis in Indian patients: Defining the entity - Sharad D Mutalik; Suresh V Pethe; Balkrishna P Nikam; Yashashree D Rasal (Wolters Kluwer Medknow Publications, 2019)
Background: Facial melanosis in tropics presents as a diagnostic and therapeutic challenge. We report characteristic patterns of facial pigmentation following vigorous rubbing or cleaning of the face in Indian patients. Awareness of the condition shall guide the clinician to a specific diagnosis. Objective: To study clinicohistopathological profile and patterns of facial frictional melanosis (FFM). Materials and Methods: A multicenter clinicohistopathological hospital-based cross-sectional case descriptive study of sixty patients with characteristic patterned facial melanosis underwent a detailed history taking and clinical examination over a period of 5 years. Biopsy specimens of thirty patients were analyzed for histopathology with hematoxylin-eosin stain. Ten biopsy specimens were also processed for both Fontana Mason and Congo red staining. Results: Sixty patients (males n = 48, females n = 12) with typical clinical features of FFM were studied. Ages of patients varied from 16 to 68 years. Patients on direct questioning confirmed history of vigorous rubbing with hand/handkerchief to clear the face of sweat and grime. Pigmentation was distributed symmetrically over the bony prominences with several characteristic patterns. Histology showed epidermal hypermelanosis, dermal melanin incontinence, and consistent absence of amyloid deposits. Conclusion: We present characteristic facial melanosis in Indian patients due to friction as a specific type of benign friction melanosis. We aim to bring to notice; friction as a distinct etiology of patterned facial hyperpigmentation.